The use of English in the social network of a student in South China: The social functions of language mixing among Chinese students. Issue 4 (20th June 2017) - Botha, Werner
Abstract : Many Chinese university students are bilingual or multilingual, increasingly switching between various Chinese language varieties and the English language (Bolton, 2013; Botha, 2014, Bolton & Botha, 2015). Bolton and Botha (2015) reported that undergraduate students at a national university in China used English for a range of social activities including 'reading', 'Internet searches', 'online socialising' and 'socializing with friends', among others. There is a need to investigate the extent to which these students actually use English in these contexts, especially in the productive use of the English language in their social lives. In examining such practices, the following questions are addressed in this article: (i) How is the English language used in the personal life of a student in Southern China; (ii) What are some of the functions of spoken and written English-Chinese code-mixing and switching between members of this student's social network; and (iii) What kind of social information is conveyed through the use of English in this student's social network? In order to examine the sociolinguistic reality of language use by these students, this article explores some of the social dynamics underlying the emerging use of English-Chinese code-switching and mixing within a particular social network: that of 'Natalie', a Chinese university student who speaks Putonghua (Mandarin, as a first language) and members within her social network, conversing within a range of modalities. This case study focuses in particular on the use of English-Chinese code-switching and mixing practices, and the extent to which these communicative practices are shaped by various social factors, ranging from the status of English as a perceived 'international' language, to aspects of stance and the affective quality of the relationships between members in this social network, to the intertextual nature of many of the linguistic instances to these practices.